Asma grave refratária em crianças e adolescentes: o grande desafio, avaliação da resposta ao corticoide a partir de parâmetros clínicos, funcionais e de marcadores não invasivos do processo inflamatório - Wenderson Clay Correia de Andrade (2014)
Objectives: To review and assess the response to systemic corticosteroids in children and adolescents with Severe Asthma. Data source: Research carried out using the databases MEDLINE and LILACS, IBECS, SCIELO, COCHRANE and EMBASE encompassing the last 15 years. Data synthesis: After researching 36 articles were selected between original and review articles that addressed the theme and assessed the response to systemic corticosteroids. Only eight original articles specifically analyzed the response to corticosteroids after 14 days of administration of prednisolone and / or after intramuscular triancinolone. The outcomes utilized were not uniform and, in most of the studies, there was no normalization of symptoms and the majority did not demonstrate normalization in VEF1, while three of them assessed VEF1 variation after the administration of a short acting bronchodilator. Four studies assessed the changing values of fractional exhaled nitric oxide and there was a decrease in values in two studies only. Just one study assessed cellularity in sputum after the administration of systemic corticosteroids, and it found that 88.2% of patients showed eosinophil percentages normalization. Conclusions: Complete response to systemic corticosteroids in children and adolescents with severe asthma is rare and little studied, and there is a need to standardize the definition of parameters to be used in assessing this response, making more studies necessary.